Impact of Universal Credit in North East England: a qualitative study of claimants and support staff. Issue 7 (4th July 2019) - Cheetham, Mandy; Moffatt, Suzanne; Addison, Michelle; Wiseman, Alice
Abstract : Objectives: To understand the impact of the roll-out of Universal Credit (UC) from the perspectives of claimants and staff supporting them in North East England. Design: Qualitative study comprising interviews and focus groups. Setting: Gateshead and Newcastle, two localities in North East England characterised by high levels of socioeconomic deprivation, where the roll-out of UC started in 2017 as a new way to deliver welfare benefits for the UK working age population. Participants: 33 UC claimants with complex needs, disabilities and health conditions and 37 staff from local government, housing, voluntary and community sector organisations. Results: Participants' accounts of the UC claims process and the consequences of managing on UC are reported; UC negatively impacts on material wellbeing, physical and mental health, social and family lives. UC claimants described the digital claims process as complicated, disorientating, impersonal, hostile and demeaning. Claimants reported being pushed into debt, rent arrears, housing insecurity, fuel and food poverty through UC. System failures, indifference and delays in receipt of UC entitlements exacerbated the difficulties of managing on a low income. The threat of punitive sanctions for failing to meet the enhanced conditionality requirements under UC added to claimant's vulnerabilities and distress. Staff reported concerns for claimants and additional pressures on health services, local government and voluntary and community sector organisations as a result of UC. Conclusions: The findings add considerable detail to emerging evidence of the deleterious effects of UC on vulnerable claimants' health and wellbeing. Our evidence suggests that UC is undermining vulnerable claimants' mental health, increasing the risk of poverty, hardship, destitution and suicidality. Major, evidence-informed revisions are required to improve the design and implementation of UC to prevent further adverse effects before large numbers of people move on to UC, as planned by the UK government.